Open versus laparoscopic appendectomy among Saudi patients - Miftah, Mohammed; Attiah, Jumanh; Alawaji, Omar; Alghamdi, Faisal; Alasmari, Abdulaziz; Elsayed, Alaa; Alfarrah, Basil; Almohideb, Malik; Majrashi, Rawabi; Al Adi, Mohammed (International Journal Of Community Medicine And Public Health, 2018)
Appendicitis is the most common cause for abdominal surgeries among all age groups worldwide. Significant research papers were published concerning the techniques through which appendectomy is done. Open appendectomy has been the gold standard treatment for acute appendicitis and has been known as a safe practice with relatively low rate of postoperative complications. However, in the last few decades, laparoscopic surgery has developed widely with the advent of minimal surgical invasion and is now more increasingly prevalent intervention. In this study, we aim to report on previous literature on laparoscopic and open appendectomies that were carried out in Saudi Arabia and compare the efficacy, safety and complications of performing laparoscopic and open appendectomies including mean operative time, mean hospital stay and prevalence of postoperative complications, mainly, wound infection and intra-abdominal infections. PubMed database and EBSCO Information Services were used for articles selection. All relevant articles to our review with the topics regarding the appendectomy procedures; both open, laparoscopic, and other articles have been used. We excluded other articles, which are not related to this field. The data will be extracted according to specific form in which it is going to be reviewed by the group members. The study found out that mean operative time was shorter in open procedures than laparoscopic one making it open appendectomy the faster intervention. Mean hospital stay was found to be significantly less in LA than OA patients. Indicated higher rate of intra-abdominal infections in the LA patients than OA ones, while wound infections are mainly present in OA cases in the reference studies.